Who pays for surgical care in the global south? A narrative review. - Sanjay Kumar Yadav; Aman Bakhsh; Dhananjaya Sharma (PLOS Global Public Health)
For decades, surgical care was sidelined in global health policy, perceived as costly, complex, and secondary to communicable disease control. However, the past two decades have witnessed a paradigm shift, with evidence highlighting surgery's critical role in addressing nearly 30% of the global disease burden. Landmark efforts like the 2015 Lancet Commission on Global Surgery and WHO Resolution WHA68.15 underscored that safe, timely, and affordable surgical care is indispensable to achieving Universal Health Coverage and the Sustainable Development Goals. Yet, despite increasing advocacy, a fundamental question remains inadequately addressed: who pays for surgical care in the Global South? This narrative review explores the current landscape of surgical financing in low- and middle-income countries, examining domestic public funding, insurance-based models, donor assistance, diaspora contributions, and the persistent burden of out-of-pocket payments. While some initiatives-such as India's AB PM-JAY and organizations like Smile Train and KidsOR-illustrate scalable financing models, most low- and middle-income countries still rely on fragmented, underfunded systems that lead to catastrophic health expenditures. Moreover, political neglect, lack of standardized surgical metrics, and low visibility within global health frameworks continue to hinder sustained investment. The review further highlights the cost-effectiveness and economic benefits of surgical interventions, positioning surgery not only as a clinical imperative but also as a strategic investment in national development. Emphasizing the emerging concept of value-based surgery, it argues for integrating frugal innovations and systems-based approaches into health financing frameworks. To achieve equitable and sustainable surgical systems in the Global South, the global health community must address the multifaceted barriers to financing-economic, structural, and political. The review calls for strategic investments, better data, and policy integration to ensure that surgical care is no longer a privilege but a universal right.